Systemic lupus erythematous in men with interstitial lung pneumonia: a rare case report - Anjani, I. Gusti Agung Dwi Putri; Saputra, I. Wayan Eka; Widyaningsih, Putu Dyah (International Journal of Advances in Medicine, 2024)
Systemic lupus erythematosus (SLE) is a chronic autoimmune inflammatory disease with unknown etiology and very diverse clinical manifestations, disease course, and prognosis. It is most common in African-American women, the prevalence being 4 per 1000 females. SLE predominantly affects young women, most presenting between 20 and 40 years of age. Male SLE is rare, with only one male patient reported per nine females. Pulmonary involvement in SLE is various. SLE-associated interstitial lung disease (ILD), while rare, is a predictor of poor prognosis. We report a 50-year-old male patient with complaints of shortness of breath, previously diagnosed with systemic lupus erythematous by examination of the antinuclear antibody (ANA) profile. The patient underwent a computed tomography (CT) scan of the thorax and the results showed interstitial lung pneumonia. The patient was given azathioprine and methylprednisolone therapy for Systemic lupus erythematous and ceftriaxone and acetylcysteine ​​for interstitial lung pneumonia.